ANALISIS PERKEMBANGAN KINERJA KEUANGAN PADA PERUSAHAAN PT PERTAMINA YANG GO PUBLIC DI BURSA EFEK INDONESIA - Widodo, Aceng; Makmur, Mariam; Nirmasari, Dian (Paser Institute Of Accounting and Finance, 2024)
The Company's financial performance is the Company's ability to run its business financially as shown in the financial statements. The good or bad financial condition of a Company can be seen from the analysis carried out on the Company's financial statements. The purpose of this study is to analyze the development of financial performance using the liquidity, solvency and profitability ratios, PT Pertamina Which Goes Public On The Indonesia Stock Exchange (2020-2022). This study uses the Descriptive Quantitative method which describes financial performance in terms of liquidity, solvency and profitability ratios. The results of this study analyze financial data, the financial performance of PT Pertamina Which Goes Public On The Indonesia Stock Exchange in terms of the liquidity ratio can be said to be liquid because it is able to pay its long-term and short-term debts. The financial performance of PT Pertamina Which Goes Public On The Indonesia Stock Exchange in terms of the solvency ratio is in poor condition because it shows a figure below the set standard. The financial performance of PT Pertamina which went public on the Indonesia Stock Exchange, when viewed from the profitability ratio, has experienced a significant increase due to the effective and efficient use of its assets.